PERBANDINGAN KADAR FLAVONOID TOTAL BUAH OYONG (Luffa acutangula L.) SEGAR DAN REBUS DENGAN SPEKTROFOTOMETRI VISIBEL - Anggraini, Devina Ingrid (JURNAL ILMIAH FARMASI SIMPLISIA, 2024)
Flavonoids are natural compounds that have ability as antioxidants. Flavonoids are found in many vegetables, one of which is the Oyong fruit (Luffa acutangula L). This study aims to determine the ratio of total flavonoid content of fresh and boiled Oyong fruit (Luffa acutangula L) using visibel spectrophotometry. Fresh Oyong fruit and boiled Oyong fruit for 5 minutes were determined qualitatively by Mg and HCl test, 10% NaOH test, concentrated H2SO4 test and quantitative test using the visibel spectrophotometry method at a wavelength of 431 nm. Comparison of total flavonoid levels can be analyzed by Independent T-test. The results of the qualitative test showed that fresh and boiled Oyong fruit positively contained flavonoids. The average level of flavonoids in fresh oyong fruit is 0.19 mgQE/ gram with a coefficient of variation of 0.40%. The average level of flavonoids in boiled oyong fruit is 0.28 mgQE/ gram with a coefficient of variation of 0.14%. The average level of flavonoids in boiled oyong fruits was significantly higher than the levels of flavonoids in fresh Oyong fruits with p<0.05.